Implikasi Metode Tarjih dalam Menyikapi Hadis-Hadis Kontradiktif - Mannan, Nuraini A (El-Sunan: Journal of Hadith and Religious Studies, 2023)
In the course of their development, scholars frequently encounter Hadiths of Prophet Muhammad SAW that appear contradictory or exhibit differences in opinion (ikhtilaf), complicating their utilization as arguments or evidence. To address this challenge, scholars have devised various methodologies, with tarjih emerging as the principal solution for resolving these discrepancies. This research aims to answer two main questions: 1) What are the principles involved in the tarjih process of Hadiths? and 2) How is the tarjih method applied to Hadiths deemed contradictory? Utilizing a literature review approach, this study collects and analyzes relevant data. It identifies seven primary principles in the tarjih of contradictory Hadiths, encompassing the investigation of narrators' conditions, the age of narration, the methodology of narration, the timing of narration, the phrasing of the Hadith, the legal content, and external factors. These findings offer new perspectives in Hadith studies, particularly in addressing disagreements related to Hadiths. ABSTRAK Dalam pengembangannya, para ulama sering kali menemukan hadis-hadis Nabi Muhammad SAW yang tampak kontradiktif atau mengalami perbedaan pendapat (ikhtilaf), yang menyulitkan penggunaannya sebagai argumen atau hujjah. Untuk mengatasi permasalahan ini, ulama telah merumuskan berbagai metode, dengan tarjih menjadi solusi utama dalam menyelesaikan ikhtilaf tersebut. Penelitian ini bertujuan untuk menjawab dua pertanyaan utama: 1) apa saja prinsip-prinsip dalam proses tarjih hadis, dan 2) bagaimana penerapan metode tarjih pada hadis-hadis yang dianggap kontradiktif. Melalui metode kepustakaan, penelitian ini mengumpulkan dan menganalisis data terkait. Hasilnya, ditemukan tujuh prinsip utama dalam tarjih hadis yang kontradiktif, meliputi penelusuran keadaan perawi, usia periwayatan, metode periwayatan, waktu periwayatan, redaksi hadis, kandungan hukum, dan faktor eksternal. Temuan ini memberikan wawasan baru dalam studi hadis, khususnya dalam menyelesaikan perbedaan pendapat terkait hadis.